Anabolic resistance assessed by oral stable isotope ingestion following bed rest in young and older adult volunteers: Relationships with changes in muscle mass. Issue 5 (October 2017) - Biolo, Gianni; Pišot, Rado; Mazzucco, Sara; Di Girolamo, Filippo Giorgio; Situlin, Roberta; Lazzer, Stefano; Grassi, Bruno; Reggiani, Carlo; Passaro, Angelina; Rittweger, Joern; Gasparini, Mladen; Šimunič, Boštjan; et al.
Summary: Background & aims: Aging and experimental bed rest are associated with muscle atrophy and resistance to post-prandial stimulation of protein synthesis or anabolic resistance (AR). We have used in young and older adult volunteers, during short-term bed rest, a quick and non-invasive method, based on a single oral bolus of the stable isotope L[ring- 2 H5 ]phenylalanine (D5 Phe), to determine post-prandial AR, defined as ratio between irreversible hydroxylation and incorporation into body protein of ingested phenylalanine. Methods: We compared in older (O, 59 ± 1 y) and young (Y, 23 ± 1 y) healthy male volunteers the effects of two-week bed rest on post-prandial protein kinetics, assessed during absorption of a standard ready-to-use oral nutritional supplement, through stable-labeled isotope amino acid D5 Phe, diluted in water, given as single oral load. The metabolic fate of D5 Phe is either utilization for protein synthesis or irreversible hydroxylation to L[ring- 2 H4 ]tyrosine (D4 Tyr). AR was defined as ratio between the areas under the curves of D4 Tyr-to-D5 Phe plasma concentrations over 6 h meal absorption. To determine the relationships between AR and muscle changes following bed rest, quadriceps muscle volume (QMV) was determined by magnetic resonance imaging (MRI). Results: At baseline, in pooled Y and O subjects, values of AR were inversely correlated with QMV (R = −0.75; p < 0.03). Following 2-weeks of inactivity, there were significant bed rest effects on AR (p < 0.01) and QMV (p < 0.03), as well as significant bed rest × group interaction for AR (p < 0.03; +9.2% in Y; +21.9% in O) and QMV (p < 0.05; −5.7% in Y; −%7.3 in O). In pooled subjects, the percentage delta changes in AR and QMV, induced by bed rest, were inversely correlated (R = −0.57; p < 0.05). Conclusion: Bed rest-induced AR is much greater in the older than in younger adults. We have developed a new, simple, non-invasive method for the assessment of AR. The results indicate that this metabolic abnormality is a key mechanism for sarcopenia of aging and inactivity. Highlights: Bed rest induces a higher anabolic resistance in older than in younger men. Anabolic resistance is a key mechanism of sarcopenia of aging. Anabolic resistance can be assessed by a new, simple, non-invasive method.